The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1016/j.ijcard.2014.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic management in Sicilian patients with definite arrhythmogenic right ventricular dysplasia/cardiomyopathy and focus on the role of implantable cardioverter-defibrillator therapy

Abstract: Arrhythmogenic Right Ventrticular Dysplasia/Cardiomyopathy (ARVD/C) is an inherited cardiomyopathy characterized by right ventricular myocyte loss with fibrofatty replacement, a high risk of ventricular arrhythmias (VA) and sudden cardiac death (SCD) [1]. Prevention of SCD represents the most important management strategy and the achievement of this target can be reached by different therapeutic strategies including implantable cardioverter-defibrillator (ICD) implantation, pharmacologic therapy, catheter abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…It usually manifests clinically with sustained monomorphic ventricular tachycardia (VT) with left bundle morphology in young individuals during exercise and can cause sudden death (SD), so the most important decision is whether or not to implant an implantable cardioverter-defibrillator (ICD) [3][4][5]. There is general agreement that ICD therapy is indicated in patients who survived an episode of ventricular fibrillation (VF) or sustained VT because of their high incidence of arrhythmia recurrences, which do not have an impact for their survival.…”
mentioning
confidence: 99%
“…It usually manifests clinically with sustained monomorphic ventricular tachycardia (VT) with left bundle morphology in young individuals during exercise and can cause sudden death (SD), so the most important decision is whether or not to implant an implantable cardioverter-defibrillator (ICD) [3][4][5]. There is general agreement that ICD therapy is indicated in patients who survived an episode of ventricular fibrillation (VF) or sustained VT because of their high incidence of arrhythmia recurrences, which do not have an impact for their survival.…”
mentioning
confidence: 99%
“…Several studies of ARVD/C probands who received an ICD showed appropriate interventions during follow-up in more than 50% of patients and approximately 40% were considered life-saving based on the presence of rapid VT/VF [8,9]. We recently reported the results of a study that investigated the therapeutic management in a group of ARVD/C patients [10]. Twenty-three patients received an ICD, and over a mean follow-up of 6.0 ± 4.4 years, 20 patients (86%) had received appropriate ICD therapy.…”
mentioning
confidence: 99%